Complications Associated With Oblique Lumbar Interbody Fusion at L5-S1: A Systematic Review of the Literature. Issue 3 (15th July 2021) - Pham, Martin H; Hassan, Omron; Diaz-Aguilar, Luis Daniel; Lehman, Ronald A
Abstract: INTRODUCTION: Oblique lumbar interbody fusion (OLIF) at L5-S1, also known as a lateral decubitus anterior lumbar interbody fusion (ALIF) or anterior-to-psoas (ATP) approach, is a technique that provides a minimally invasive corridor to a key segment in the spine for degenerative conditions and deformity correction. However, the evaluation of complications associated with this level has been difficult as prior reports include other levels that have different anatomic considerations. OBJECTIVE: To present a systematic review of previously reported cases of OLIF, lateral ALIF, and an ATP approach at L5-S1 to discuss their associated complications. METHODS: Following preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines, a PubMed search was performed up to January 2021 to identify literature describing OLIF, lateral ALIF, and ATP approaches involving the L5-S1 levels. A quality assessment with risk of bias analysis was performed using the methodological index for non-randomized studies (MINORS) assessment tool for each study. Data we then extracted to identify all complications. RESULTS: The initial search yielded 532 publications. After screening, there were 18 studies with 553 total patients who underwent OLIF including L5-S1. Analysis of these studies demonstrated a vascular complication rate of 2.5%, bowel-associated complication rate of 0.5%, ureteral injury rate of 0%, neurological injury rate of 1.9%, pseudarthrosis rate of 7.3%, and reoperation rate of 2.2%. CONCLUSION: The L5-S1 level remains an important target for sagittal alignment in both degenerative and deformity surgery. The OLIF surgical corridor to this level presents special anatomic and clinical considerations and is a safe approach to minimize morbidity with minimally invasive access.